The Musculature of Coleoid Cephalopod Arms and Tentacles - Kier, William M. (Frontiers in Cell and Developmental Biology, 2016)
The regeneration of coleoid cephalopod arms and tentacles is a common occurrence, recognized since Aristotle. The complexity of the arrangement of the muscle and connective tissues of these appendages make them of great interest for research on regeneration. They lack rigid skeletal elements and consist of a three-dimensional array of muscle fibers, relying on a type of skeletal support system called a muscular hydrostat. Support and movement in the arms and tentacles depends on the fact that muscle tissue resists volume change. The basic principle of function is straightforward; because the volume of the appendage is essentially constant, a decrease in one dimension must result in an increase in another dimension. Since the muscle fibers are arranged in three mutually perpendicular directions, all three dimensions can be actively controlled and thus a remarkable diversity of movements and deformations can be produced. In the arms and tentacles of coleoids, three main muscle orientations are observed: 1) transverse muscle fibers arranged in planes perpendicular to the longitudinal axis; 2) longitudinal muscle fibers typically arranged in bundles parallel to the longitudinal axis; and 3) helical or obliquely arranged layers of muscle fibers, arranged in both right- and left-handed helixes. By selective activation of these muscle groups, elongation, shortening, bending, torsion and stiffening of the appendage can be produced. The predominant muscle fiber type is obliquely striated. Cross-striated fibers are found only in the transverse muscle mass of the prey capture tentacles of squid and cuttlefish. These fibers have unusually short myofilaments and sarcomeres, generating the high shortening velocity required for rapid elongation of the tentacles. It is likely that coleoid cephalopods use ultrastructural modifications rather than tissue-specific myosin isoforms to tune contraction velocities.